2015
DOI: 10.14685/rebrapa.v6i1.177
|View full text |Cite
|
Sign up to set email alerts
|

UV spectroscopy and multi-product multivariate calibration in the determination of the total acidity in industrialized juices

Abstract: <p>The determination of the total acid using UV spectroscopy and multi-product multivariate calibration is presented as an alternative to the conventional method through potentiometric titration. The model was developed including different products (fruit nectar of different flavors and light fruit nectar) where outliers samples were identified and excluded. Partial least squares (PLS) regression was used in order to build the model. Accuracy, represented by the values of the Root Mean Squared Errors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Correlation coefficient to the fit of the multiproduct model, presented by plotting the reference values against the estimated values, was 0.7188 for vitamin C and 0.7435 for total acidity. These values were considered satisfactory since previous research reported coefficient values around 0.7, when the reference method was the titration method (Valderrama, Braga, & Poppi, 2007a;2007b;Ferreira, Pallone, & Poppi, 2013;Santos et al, 2015;2016). The results presented in Table 2 and Figure 2 show that the multi-product PLS model results in more 'dispersed' results for vitamin C, which may be justified by the fact that the vitamin C is oxidized quickly, when in the presence of oxygen.…”
Section: Parameters Of Merit Equationmentioning
confidence: 62%
See 3 more Smart Citations
“…Correlation coefficient to the fit of the multiproduct model, presented by plotting the reference values against the estimated values, was 0.7188 for vitamin C and 0.7435 for total acidity. These values were considered satisfactory since previous research reported coefficient values around 0.7, when the reference method was the titration method (Valderrama, Braga, & Poppi, 2007a;2007b;Ferreira, Pallone, & Poppi, 2013;Santos et al, 2015;2016). The results presented in Table 2 and Figure 2 show that the multi-product PLS model results in more 'dispersed' results for vitamin C, which may be justified by the fact that the vitamin C is oxidized quickly, when in the presence of oxygen.…”
Section: Parameters Of Merit Equationmentioning
confidence: 62%
“…The total acidity (mg 100 mL -1 ) was determined, in triplicate, according to the Federation International des Producteurs de Jus de Fruit (2005) and to the methodology described by Santos et al (2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations